(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The present work points to reconstruct the definition of human embryo in art. 6, par. 2, letter. c) of Directive 98/44/EC on the legal protection of biotechnological inventions, as outlined by the Court of Justice, preliminary, in Brüstle of 2011 and, most recently, in the decision of December 2014, International Stem Cell Corporation. It will highlight, also, potential practical implications that these judgments may exercise in scientific research on human embryos, in light of European legislation on the promotion and financing of scientific progress. We will question, however, on the legality of the pursuit of technological development and scientific practice when must relate to living matter and the possible configurability of an effective compromise between the free exercise of science and the respect of human dignity. Finally, we will attempt to reconstruct the role assumed by the judge - in this case, the European court - in the socio-political debate in determinating the “bioethics rights” and in possible relationships between science and law, aimed at the constant balancing of interests ethically and scientifically oriented.